Ideological Apparatuses of Shari’a and Reproduction of Domination: A Critique on the Book The Circles of Fear - Reza Najafzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In this manuscript, we try to examine the connection between the interpretation of the sacred text, the ideology of language, and the apparatuses of domination in Abu Zayd`s “Circles of Fear: Reading the Discourse about Women” with a focus on the issue of women. “Circles of Fear” is based on the text-based historical hermeneutics and Abu Zayd has a post-secular humanistic approach. In “Circles of Fear” he has used critical approaches such as subaltern theory and critique of ideological apparatuses within the framework of historical structuralism, and in addition to his Qur'anic views, he has also developed a kind of critical political sociology. In Abu Zayd’s critical theory, the abstractedness of the situation arises from the intertwined relations of Shari'a, political economy, and ruling power. In his analysis, we can see a net of power that overshadows the exploitative financial and economic relations and the interpretation of Sharia and with its repressive mechanisms, prevents critical awareness in the social space. This refusal of awareness in the Egyptian space is more severe and worse for women. This article reviews Abu Zaid’s views critically in five parts: Abu Zaid and critical theory of society; reconstruction of reawakening discourse and the history of Etzali belief; women in crisis discourse, the ideology of language and the production of domination; the defeat and historical decline and critique of anti-woman practices and discourses on the eve of the transition to the information age; and the critique of the commodification of women.